2008
DOI: 10.1108/02610150810897264
|View full text |Cite
|
Sign up to set email alerts
|

An overview of the UK Employment Appeal Tribunal decisions in sexual harassment cases 1995‐2005

Abstract: Purpose -The purpose of this paper is to present research conducted with legal cases of sexual harassment (SH) in Great Britain over the past ten years. The paper contributes to the equal opportunities literature since it offers a rare interpretation of longitudinal case data with important implications for law, policy, social science and, indeed, for the management of equal opportunities within organizations. The paper approaches SH both as an evolving legal issue and as a type of organizational conflict, wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
7
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 36 publications
2
7
0
Order By: Relevance
“…In New Zealand, 42 per cent of women in frontline hospitality roles are aged under 25 years (Whiteford and Nolan, 2007), and probably enjoy the lively and social environment of a hospitality workplace (Guerrier and Adib, 2000). However, young women are reluctant to complain of harassment in case of reprisals from customers and/or managers (Rosenthal et al , 2008), leaving a large proportion of hospitality workers vulnerable to abuse, and due to their personalities and ages, likely to attract it. Kensbock et al (2015) also found that youth and inexperience rendered workers more vulnerable to harassment, as these employees were unable to deal with difficult situations.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In New Zealand, 42 per cent of women in frontline hospitality roles are aged under 25 years (Whiteford and Nolan, 2007), and probably enjoy the lively and social environment of a hospitality workplace (Guerrier and Adib, 2000). However, young women are reluctant to complain of harassment in case of reprisals from customers and/or managers (Rosenthal et al , 2008), leaving a large proportion of hospitality workers vulnerable to abuse, and due to their personalities and ages, likely to attract it. Kensbock et al (2015) also found that youth and inexperience rendered workers more vulnerable to harassment, as these employees were unable to deal with difficult situations.…”
Section: Discussionmentioning
confidence: 99%
“…Agrusa et al (2002) described restaurant employees as 'outgoing, personable and energetic ' (p. 29) and posited that this explains the high levels of sexual harassment in their industry. Many young women working in hospitality tolerate verbal comments, touching, sexual harassment and physical abuse from customers because they may perceive they have no choice (Poulston, 2008a, Rosenthal et al, 2008. However, more experienced employees are better at distinguishing between their work and personal selves (Yagil, 2008), so are less vulnerable.…”
Section: Influences On Sexual Harassment In the Workplacementioning
confidence: 99%
See 1 more Smart Citation
“…An analysis of EAT cases reveals that the majority of appeals are lodged by the claimant and that the most common ground for the appeal is based on the claim that the employment tribunal erred in its application of the law. The majority of appeals 40 per cent were dismissed (Rosenthal et al , 2008).…”
Section: Employer Defencementioning
confidence: 99%
“…Aston 2000; Clarke 2006; Conaghan 2002; Dickens 2002; Gibbons 2007; Earnshaw 1993; Leonard 1987; Lewis and Clark 1993; McCrudden et al . 1991; Rosenthal et al . 2008; Samuels 2004).…”
Section: Analytical Framework For the Studymentioning
confidence: 99%